2010
DOI: 10.1007/s10811-010-9547-1
|View full text |Cite
|
Sign up to set email alerts
|

Commercial extract from the brown seaweed Ascophyllum nodosum reduces fungal diseases in greenhouse cucumber

Abstract: This study examined the effects of Stimplex™, a marine plant extract formulation from Ascophyllum nodosum, on some common cucumber fungal pathogens. Greenhouse cucumber plants were sprayed and/or root drenched using Stimplex™ at 0.5% or 1% concentration twice at 10-day intervals. Treatments also included application of fungicide (chlorothalonil, 2 g L −1 ) alternating with Stimplex™ application. Treated plants were inoculated with four cucumber fungal pathogens including Alternaria cucumerinum, Didymella appla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
89
3
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(118 citation statements)
references
References 35 publications
16
89
3
4
Order By: Relevance
“…In our study the application of a cold process seaweed extract increased the phytochemical levels in broccoli plants. The enhanced accumulation of phenolic compounds may be related to an increased activity of phenylalanine ammonia lyase (PAL) and peroxidases (PO) enzymes which cause an increase in the available phenolic free pool (Jayaraman et al 2011). It is well documented that increase in phytochemical compounds can be affected by many factors such as light, water, CO 2 , methyl jasmonate, abiotic stress factors such as water deprivation (Guo et al 2011).…”
Section: Total Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study the application of a cold process seaweed extract increased the phytochemical levels in broccoli plants. The enhanced accumulation of phenolic compounds may be related to an increased activity of phenylalanine ammonia lyase (PAL) and peroxidases (PO) enzymes which cause an increase in the available phenolic free pool (Jayaraman et al 2011). It is well documented that increase in phytochemical compounds can be affected by many factors such as light, water, CO 2 , methyl jasmonate, abiotic stress factors such as water deprivation (Guo et al 2011).…”
Section: Total Yieldmentioning
confidence: 99%
“…More research is needed to elucidate the action mechanisms of seaweed extracts and the elicited physiological responses on plants as well as the interactions between plant/pathogen attack in plants with increased levels of phytochemicals. The advantage of using seaweed extracts is that it may help the plants respond to biotic and abiotic stress better, besides promoting plant growth (Jayaraman et al 2011). The prolonged application of seaweed extract can significantly increase the amount of total phenolics, flavonoids and isothiocyanates.…”
Section: Total Yieldmentioning
confidence: 99%
“…Furthermore, cucumber plants grown under greenhouse condition and sprayed and/or drenched with 0.5 and 1% (v/v) of Ascophyllum nodosum extracts showed decreased incidence of Fusarium wilt caused by F. oxysporum f. sp. cucumerinum [40]. In a recent study, Guesmi [27] found that S. vulgare methanolic extract, tested at 0.5 and 1 g/L, suppressed leaf damage index (96%) and the vascular discoloration extent (100%) caused by Verticillium dahliae infection on tomato and eggplant plants, compared to the untreated controls.…”
Section: Discussionmentioning
confidence: 99%
“…Three foliar applications of 0.2% SWE reduced Alternaria radicina and Botrytis cinerea infections in carrots by 57% and 53.5%, respectively [130]. Greenhouse cucumbers treated with foliar or root drench applications of 0.15 or 0.3 ml of SWE at 3 10-day intervals had reductions in the severity of the fungal diseases Alternaria cucumerinum, Didymella applanata, Fusarium oxysporum, and Botrytis cinerea [146]. However, the SWE Marinure applied at the m anufacturer's recom m ended rates had no im pact on soil -borne diseases of tomatoes [94].…”
Section: Whapham (1994) Observed That Tomato Plants Receiving Root Drmentioning
confidence: 97%
“…Olive trees treated with two wintertime applications of 17.5 ml SWE/tree developed color sooner than untreated trees [117]. Foliar SWE applications resulted in greater total phenolics in carrots [130] and cucumbers [131]. SWE typically does not influence TSS, pH, or TA of strawberries [127], watermelons [128], oranges [132], or mandarins [124].…”
Section: Effects Of Fish-based Fertilizer On Cropmentioning
confidence: 99%